Prevalence and Genetic Analysis of Porcine Circovirus 3 in China From 2019 to 2020 - Ge, Meng; Ren, Jie; Xie, Yi-Lin; Zhao, Dun; Fan, Fang-Cheng; Song, Xiao-Qin; Li, Man-Xiang; Xiao, Chao-Ting (Frontiers in Veterinary Science, 2021)
Porcine circovirus type 3 (PCV3), a virus belonging to the Circoviridae family, is considered to be associated with respiratory and neurological signs, cardiac and multisystemic inflammation, reproductive failure, and porcine dermatitis and nephropathy syndrome-like disease in pigs (Sus scrofa). In this study, epidemiological and serological investigations of PCV3 in clinically healthy pigs from different regions of China were performed. Overall, 42.87% (1101/2568) of pigs were positive for PCV3 Cap antibody via indirect enzyme-linked immunosorbent assay, with a higher prevalence of PCV3 in multiparous sows (62.22%, 881/1416) and fattening pigs (28.96%, 159/549) than in suckling piglets (8.96%, 32/357) and nursery pigs (11.79%, 29/246). Of the 2568 samples, 255 were further tested for PCV3 DNA using real-time polymerase chain reaction, and 63.14% of these were positive, with nearly half having less than 10 virus copies. The PCV3 DNA and antibody positivity rates were high in the pig serum samples; however, the virus titers and antibody levels were both low, indicating that the humoral immune response of PCV3-infected pigs was weak or lagging, and persistent or repeated infections could occur. Additionally, the complete genomes of 23 PCV3 strains were sequenced and analyzed, which showed nucleotide identities of 98.5~100.0%, 98.6~100.0%, and 99.2~100.0% in the complete genome, open reading frame (ORF)2, and ORF1 sequences, respectively, and amino acid identities of 96.7~100.0% and 99.3~100.0% in the capsid and replicase proteins, respectively. Phylogenetic analysis based on ORF2 nucleotide sequences indicated that the PCV3 strains obtained in the present study could be classified into three sub-clades, with most strains clustered into clade 3c, indicating that PCV3c is the dominant subtype in the regions of China investigated. In general, the present study revealed a high prevalence and high genetic divergence of PCV3 among Chinese pig herds, and indicated that the potential effect of PCV3 on the pig industry may be a concern.